Hubungan Daya Ledak Otot Tungkai Terhadap Keterampilan Shooting Ekstrakurikuler Sepak Bola Smpn 18 Bengkulu Selatan - Apendi, Mirwan; Apriansyah, Dolly; Ertanto, Dody (CV. Generasi Insan Rafflesia, 2024)
This study aims to the relationship of leg muscle explosive power to extracurricular soccer shooting skills of SMPN 18 South Bengkulu with a type of correlation research using test and measurement methods and documentation. The population in this study were extracurricular players with sampling using total sampling techniques totaling 20 players. The results of research on the relationship between limb muscle explosive power and soccer extracurricular shooting skills of SMPN 18 South Bengkulu are 0.34 in a sufficient category position. While the ttable value is determined based on the level of significance (α) is 5% used and the degree of freedom (d.f = n-2) whose sample size (n) is 20, then d.f = 20-2 =18 based on the distribution of the ttable obtained 1.09. The decision is taken by comparing the tcount value with the ttable. If tcount is smaller than ttable, then the decision accepts the Ho hypothesis. And vice versa if the tcount is greater than the ttable then reject Ho and accept Ha, in this test, the tcount is 1.6 greater than the ttable is 1.093, so the decision rejects the null hypothesis (Ho) and accepts the alternative hypothesis (Ha). In the normality and homogeneity test. Leg muscle explosiveness obtained the result X² is 3.1 ≤ from x² table 32, 671 which means normal distribution. Shooting skills obtained results x²count 5 ≤ x²tabel 32, 671 which means normal distribution. The homogeneity test results get the results of Fcount is 1.7 and Ftable is 2.12. Means Fhitung 1.7 < Ftabel 2.12 then the data distribution is Homogeneous.